Perlindungan Hukum terhadap Investor pada Jual Beli di Pasar Modal dalam Perspektif Islam - Bonaraja Purba; Riky Aulia Rachman Marpaung; Dicky Effendi; Rizky Fadly (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to examine and analyze the legal protection given to investors in buying and selling shares in the capital market from an Islamic perspective. The research methodology used is descriptive analysis, which involves comprehensive data collection regarding the characteristics of a particular situation or symptom that contributes to strengthening the theory of Islamic capital markets. In this case, the author uses a document or literature study as a legal material collection technique, by reviewing the literature related to the research topic. This approach aims to obtain secondary data from sources such as the Quran, hadith, MUI fatwa, and relevant laws and regulations, especially Law No. 8 of 1995 concerning Capital Markets. The findings of this study reveal that the legal protection of investors in buying and selling activities in the capital market in an Islamic perspective is based on the principles of transparency and openness, the existence of a Sharia Supervisory Board (DPS), sharia audits, dispute resolution mechanisms, and the prohibition of ribawi practices or usury-based transactions.